Os filmes infantis e suas implicações para a formação da criança - Tavares, Moizaquer Moraes (2019)
This work investigated the relationship between media and curriculum, some authors collaborated to better understand the theme, among them: Henry Giroux (2003), Douglas Kellner (2001), Silva (1995) and Costa (2009). understanding of the subject. Given the validity of the subject and starting from the conjuncture of the current political scenario, where the media culture is approached as a strong instrument by which manipulates and forges many thoughts, came the desire to explore its effects on children. Taking into account that children's films, cultural artifacts dissipating media culture, enter millions of homes as a means of children's entertainment, the question arose: "In what way has the media curriculum implicated in the training of children in childhood?" is to reflect on the effects of the media curriculum on the training of children in childhood. The plots of some films were analyzed, such as: "Viva! Life is a party (2018) "," Up! (2010), "How to Train Your Dragon (2010)" and "Emoni - The Movie (2017)" as they are well-liked films by children. The work also sought to present historical aspects about the emergence of the media, its tendencies and contributions that it brought to the development of society. In order to do so, we used bibliographical research focusing on the results of pertinent theorization, followed by systematization, analysis of ideas and images in cultural artifacts. It was concluded that children's films can be great teaching tools, since there is a concern on the part of the teacher / educator to choose the film according to the age group of the students and reflecting before on the content of the film and what one wants teach. It has been found that there are undesirable consequences due to the fact that children's films are not seen / used as useful tools to construct criticality in children in their school and social development process, that is, movies may be used only for entertainment . It has been found that the cultural industry is extremely strong and that its products are produced for specific purposes of trade and consumption easily accepted by the children's audience. It was noticed that the content of films can often lead children to behave in a non-childlike way. This we can call childhood adultery, or instant childhood. However, the films offer great tools that can directly aid in the imaginary development of the child. Cultural artifacts (re) construct standards by affirming / reaffirming / confirming norms and ideas accepted by society. It was also observed that cultural artifacts, materialized in the form of children's films, need to be seen as a curriculum that teaches values, beliefs that constitute constructive instruments that forge identities positively, or negatively, depending on how this tool was used . Parents, educators need to contribute to the critical construction of children, making them active citizens emancipated in their reality.